PENGARUH TINGKAT LITERASI PERPAJAKAN, PERSEPSI PERPAJAKAN, DAN DIGITALISASI SISTEM PERPAJAKAN TERHADAP NIAT PATUH PAJAK PADA GENERASI Z - Intan Salsabila; Rahmat Kurniawan (Mount Hope Economic Global Journal, 2024)
The study aims to test and demonstrate the influence of tax literacy levels, tax perceptions, and digitization of tax systems on tax compliance intentions in Generation Z. The study was conducted using explanatory quantitative methods and involved 100 respondents from the 2018 and 2019 categories at the University of Andalas. Data collection is done by distributing questionnaires offline and online. At the same time, the level of tax literacy, tax perception, and digitization of tax systems influenced tax compliance, the results of this study also showed that there was no difference between students who received tax education and students who did not receive tax education to have the intention to comply with their tax obligations. These findings indicate that there are other factors that influence a person's desire to meet future tax obligations. This research provides a reference to future researchers in finding other variables that affect a person's intention to comply with taxes, and as reference for the Directorate-General of Taxation (DJP) in optimizing a work programme that focuses on improving compliance in the future.